The Probiotic Properties of Lactobacilli in Organic Pigs - D. Liu; K. Direksin; M. Panya (Tropical Animal Science Journal, 2022)
Indigenous Lactobacilli are suitable probiotics because they adapt well in the hosts and ecological niches. Here we test local Lactobacillus for future application in the pigs as the farm-autogenous strains. The objectives of this study were to evaluate the probiotic properties of Lactobacillus isolated from the feces of antibiotic-free organic pigs. The properties include bile salt and pepsin tolerance, survival in storage (37 & 4 oC) and probiotic-packaging (50 oC) temperatures, antibiogram, and antagonistic activity against Salmonella typhimurium ATCC 13311 and Escherichia coli ATCC 25922. Eighteen isolates with three different species were tested in this study as follows: L. reuteri (seven strains), L. mucosae (ten strains), and L. plantarum (one strain). Four isolates—L. reuteri-OP1, L. mucosae-OP2, L. mucosae-OP3, and L. reuteri-OP17—had good in vitro probiotic characteristics. Eleven isolates completely inhibited both E. coli and S. typhimurium. The other isolates are perfectly disabled, either E. coli or S. typhimurium. Despite that, they caused a reduction in the numbers of each pathogen. All Lactobacilli tested were susceptible to amoxicillin-clavulanate, ampicillin, and imipenem. Most isolates were sensitive to clindamycin (72%), gentamicin (56%), and tetracycline (50%). Half of the proportions were somewhat sensitive/resistant to cefotaxime (39/44%), tetracycline (50/39%), and streptomycin (39/56%). One hundred percent of Lactobacilli were resistant to norfloxacin, sulfamethoxazole-trimethoprim, and vancomycin, while 94% were resistant to enrofloxacin. Most of the local Lactobacilli passed in vitro tests, but the efficacy of probiotics in pigs awaits further in vivo investigation. Therefore, the potential probiotic strains derived from this study could be selected for further evaluation of their probiotic roles in economic pigs.